(untitled) (The Research of Medical Science Review, 2025)
Patients with cancer need better nutrition and metabolism care to survive and recover because these problems hurt both. These conditions decrease how well treatments work and increase health problems after surgery happens. These problems emerge mainly from inflammation and loss of appetite. What was once impossible in treating cancer patients now becomes possible through artificial intelligence which includes machine learning and deep learning systems. These systems show excellent potential for revolutionizing cancer healthcare. AI uses patient data for accurate diagnosis by modeling outcomes from medical files and visual scans while selecting genetic information. The system analyzes health data from genes, everyday life, and healthcare to understand what and how patients eat then gives individual meal suggestions based on patient needs. Researchers like ACPs more than standard treatment because they destroy cancer cells specifically and create few drug resistance traits. Through our plan this paper demonstrates how AI combined with data analysis can optimize cancer care by creating medicine development methods linked to patient-specific nutrition plans. Artificial Intelligence (AI) changes cancer treatment methods by using data analysis to identify particular genetic factors and medical histories in patients thus producing precise diagnostic conclusions as well as customized treatment procedures. The AI platform COMBI indicates suitable treatments to healthcare providers while ASCAPE showcases enhanced chemotherapy dosing capability which improves total care effectiveness. Researchers have investigated anticancer peptides (ACPs) as an emerging treatment approach against solid tumors because these peptides use different membrane interaction models to destroy cancer cells without developing resistance. Medical experts lead extensive clinical studies about cationic molecules to research their potential for restricting tumor growth together with their potential to prevent cell migration and blood vessel formation at minimum toxic levels and high precision.